2015
DOI: 10.1016/j.jtcvs.2014.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic effects of left pulmonary artery stenosis after superior cavopulmonary connection: A patient-specific multiscale modeling study

Abstract: The effects of <65% stenosis on SCPC hemodynamics and physiology were minor and may not justify the increased complexity of adding LPA arterioplasty to the SCPC operation. However, in the longer term, pulmonary augmentation may affect outcomes of the Fontan completion surgery, as pulmonary artery distortion is a risk factor that may influence stage III physiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 26 publications
2
17
0
1
Order By: Relevance
“…Larger numbers of Fontan patients with KE are needed to see if the diastolic plateau pattern is related to other clinical parameters than APC flow. Recently, Schiavazzi et al used modeling to calculate the effects of left pulmonary artery stenosis on hemodynamics in single ventricles stage II surgery and found that the stenosis needed to be quite severe, >65% of the diameter, to be hemodynamically significant [33]. This is in line with the findings of unchanged ventricular KE pattern before and after stenting of a left pulmonary stenosis in one of our study patients.…”
Section: Discussionsupporting
confidence: 87%
“…Larger numbers of Fontan patients with KE are needed to see if the diastolic plateau pattern is related to other clinical parameters than APC flow. Recently, Schiavazzi et al used modeling to calculate the effects of left pulmonary artery stenosis on hemodynamics in single ventricles stage II surgery and found that the stenosis needed to be quite severe, >65% of the diameter, to be hemodynamically significant [33]. This is in line with the findings of unchanged ventricular KE pattern before and after stenting of a left pulmonary stenosis in one of our study patients.…”
Section: Discussionsupporting
confidence: 87%
“…This is likely due to the abundance of target quantities available in the proximity of the aortic capacitor (i.e., cardiac output, minimum, average and maximum aortic pressures). Values of C ao estimated by DREAM were also found to be compatible to those determined from manual tuning in previous work from our research group [57]. …”
Section: Resultssupporting
confidence: 84%
“…For such couplings, SimVascular contains an efficient and stable numerical scheme for implicitly coupling ODE models with the flowsolver for the 3D domain without significantly increasing the overall simulation cost, 18,35 which has been used in several recent applications. 25,54 …”
Section: Methodsmentioning
confidence: 99%